Effect of Abiotic Stress Conditions on Growth and Sporulation in Mycopesticidal Isolates of Beauveria species - P C, Padmini Palem (International Journal of Pharmaceutical & Biological Archive, 2013)
Effect of Abiotic Stress Conditions on Growth and Sporulation in Mycopesticidal Isolates of Beauveria species